Health Problems Associated With Display Screen Equipment Use - Golda O. , Ekenedo; Jonathan , Blessing Nkiruka (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
Workers are often vulnerable to some unhealthy conditions that are inherent in their work processes and work environment. The emergence of computer technology created new jobs, but also introduced fresh health concerns for the users. Workers whose job requires constant use of Display Screen Equipment (DSE) are at particular risk of certain health problems including Musculoskeletal Disorders (MSDs) which are diseases that affect the muscular and skeletal systems, headaches, eye problems and stress. The paper discusses these health problems, their signs and symptoms, preventive measures and management. It identifies that employers and employees can play reasonable roles towards preventing and reducing the occurrence of DSE-related health problems among workers through organizational and administrative interventions, ergonomic interventions, personal interventions and behavioural interventions. The paper finally suggests among others that while employers should implement interventions aimed at preventing and reducing DSE-related health problems, the government should develop policies and regulations that protects workers who use these equipments just as is obtained in developed nations